Psycholinguistic Concept and the Model of Speech Influence by A.A. Leontiev and Its Importance for Actualization of the Modern Communication Problems - Ksenia Maksymenko; Heorhii Kalmykov (Психолінгвістика)
The article reveals the main provisions of the concept of speech influence and describes its theoretical model, which was developed by well-known psycholinguist of the 20th century A.A. Leontiev. The main ideas of this concept are explicated within the scope of the problem of speech communication and conditioned by this verbal act processes of speaking of the communicator (speaker) and listening of the recipient (s). The speech influence is considered by the researcher of this problem at the level of the internal and external stages of the communicative-speech processes generation of the speaker and the recipient. That is why A.A. Leontiev pays great attention in this concept to the analysis of such psycholinguistic phenomena as: «value», «sense», «semantic field of the recipient», «sign», «internal speech», «internal programming», «act of speaking» etc. The article reveals the following aspects: a) established by A.A. Leontiev evolution of the forms of communication and its psychological and semiotic mediation; b) separated by him stages of the historical formation of the activity of communication, in particular its final stage – the speech effect, which becomes a professional activity, motivated «from inside the self»; c) distinguished by the researcher notions of «speech» and «speech activity», d) defined by him the notion of «communication» and its varieties, e) associated with orientation – the criterion of speech communication – speech effect, which is characterized as one of the aspects of psychological content of communication, g) identified by three parameters phenomenon of the sign and applied in its interpretation two methods of scientific analysis important for a deep understanding of speech influence used, through the processes of understanding (the transition from a sign to the thought) and through the objectification of the subjective communicative intention (the transition from a thought to the sign) and other important provisions of the proposed concept. The content of this manuscript also describes the psycholinguistic model of speech effect, which, according to the author, has statuses or psychological actions, or appears as an independent activity with its own motive, has a feedback, acts in various forms of interference with consciousness and subconscious of the personality, etc.; the ways of achieving changes in the recipient’s existing values under the influence of the content of communicator’s speech are represented; the three-layer psycholinguistic structure of the speech influence is substantiated. In the debating section of the article, it is suggested to consider the scientific work of A.A. Leontiev concerning the speech influence as a psycholinguistic theory, by taking into account its theoretical and practical significance for modern science and communicative practice.